Digital dilemmas: the unintended consequences of election technology. Issue 8 (17th November 2018) - Cheeseman, Nic; Lynch, Gabrielle; Willis, Justin
ABSTRACT: Digital technologies are increasingly used in elections around the world. Where the resources and capacity of the state are limited, some have argued that such technologies make it possible to rapidly "leapfrog" to cleaner and more credible elections. This article argues that the growing use of these technologies has been driven by the fetishization of technology rather than by rigorous assessment of their effectiveness; that they may create significant opportunities for corruption that (among other things) vitiate their potential impact; and that they carry significant opportunity costs. Indeed, precisely because new technology tends to deflect attention away from more "traditional" strategies, the failure of digital checks and balances often renders an electoral process even more vulnerable to rigging than it was before. These observations are not intended as a manifesto against the digitization of elections; apart from anything else, we argue that the drivers of the adoption of these new methods are too powerful to resist. But the analysis draws attention to the importance of more careful assessments of the problems, as well as the benefits, of such technologies – and to the need for more careful planning in their deployment.